Pergulatan Kelompok Civil Islam Arus Utama dan Sempalan dalam Ranah Private, Public, Market, dan State: Pendekatan Sosiologis - Adeni Adeni; Nur Hamid (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2020)
The presence of the new Islamic civil society movement, which is generally represented by the salafism ideology, is a challenge for mainstream Islamic organizations such as NU and Muhammadiyah. The new Islamic civil group called the splinter moves massively in four main social domains, namely private, public, market, and state. By using a qualitative method based on the sociological approach, this article will answer how the struggle between the mainstream Islamic civil groups and splinter civil groups in these four domains. This study concludes that the discourse of Islamic civil society in Indonesia today is very complex. Discourse does not only occur between state and non-state, but also between fellow Islamic civil groups. They contest each other in developing the private sphere, showing their existence in the public sphere, controlling and developing economic/market resources, and involving themselves in government/politics. Each group has their respective strategies in displaying their role so that it often causes friction. This condition requires open communication, mutual understanding and cooperation between all Islamic civil groups.